Diversified Talent Cultivation Mechanism of Early Childhood Physical Education Under the Full-Practice Concept – Oriented by Preschooler Mental Health and Intelligent Teaching - Wang, Nina; Rahman, Mohd Nazri Bin Abdul; Daud, Megat Ahmad Kamaluddin Bin Megat (Frontiers in Psychology, 2021)
To level up the early childhood physical education, oriented by preschooler mental health, the talent cultivation mechanism for undergraduates is explored under the “full-practice” concept. First, from the perspective of preschooler psychology, the mechanisms of ability training and talent cultivation for undergraduates majoring in early childhood education are explored under the “full-practice” concept. Considering that the physical, psychological, and intellectual development of preschoolers shall follow the rules of physical education, while the current early childhood education China mainly focuses on intelligence education, the early childhood physical education is analyzed further. By investigating the undergraduate major of early childhood education in Henan University, the current problems of the early childhood education system in universities are summarized. Then, combined with the form of physical education in kindergartens, strategies for talent cultivation and curriculum setting of early childhood physical education major in colleges and universities are proposed. The results show that of all the courses for the early childhood education major, compulsory courses account for 81.2%, and optional courses account for 18.8%. A survey of undergraduates' attitudes towards the curriculum of their major finds that 81.2% of the undergraduates have thought that the types and contents of practical courses should be increased. This shows that undergraduates majoring in early childhood education are dissatisfied with the current curriculum system, especially the increase in demand for practical courses. Early childhood physical education is vital in the system of early childhood education. In terms of its talent cultivation, the "full-practice" concept helps combine theory with practice to improve the effectiveness of education and teaching, pushing forward the reform of the education system. In addition, considering that the intelligence, data, and network will be the new development direction of modern physical education, the tracking and monitoring of children's physical education teaching in China is an important link. Through the continuous introduction of wearable artificial intelligence products, children's physical fitness can be monitored and scientific management of their sports activities can be implemented, which has far-reaching significance for promoting campus sports in colleges and universities.